Practical guide to structuring the Discussion section in clinical and epidemiological studies - Charlotte Leboeuf-Yde; Claire Gudex (Chiropractic & Manual Therapies, 2026)
Abstract This is the last of three articles that provide step-by-step guides on how to structure the content of a scientific article to ensure a coherent and relevant text. The current article aims to help authors produce relevant and stringent Discussion sections that reflect clarity of thought and critical analysis, with contents driven by the research objectives. We first describe the purpose of the six typical elements of the typical Discussion section: (i) Summary of Findings, (ii) Explanation of Findings, (iii) Comparison of own results with other studies, (iv) Critique of own work, (v) Perspectives, and (vi) Conclusion. We show different placements and combinations of these and explain what they should include. We then suggest how to write a simple Summary of Findings and how to avoid re-writing the Background section in the Explanation of Findings. We show how to use the previously identified research gaps when comparing own results with similar studies, suggest different approaches for Critique of own work, define the types of Perspectives that are common in clinical and epidemiological studies, and explain how to provide relevant and memorable information in the Conclusion. Examples of how authors have dealt with different elements of the Discussion section have been selected from this journal. Finally, we discuss the use of artificial intelligence in the writing process. We hope that the three articles will help authors to plan their writing in a meaningful manner, thus saving time for themselves and resulting in articles that are easy to read and understand.